The Correlation Between Work Environment And Psychosocial Hazards With Work Stress In Nurses At The Hospital - Yunina Elasari; Yosi Hafid Muammar; Moh Heri Kurniawan; Rizki Yeni Wulandari (Health Research Journal of Indonesia, 2026)
Nowadays, work stress has become a global issue that affects all professions and workers. The health sector is a field where work stress is very common among health workers. All hospital workers are professionals who are susceptible to stress. However, stress levels in nurses tend to be higher. By paying attention to the work environment, employees will be motivated to work enthusiastically to achieve optimal job satisfaction. In addition, psychosocial hazards in the workplace can affect physical and psychological conditions. This research objective was to determine the correlation between the work environment and psychosocial risks with the stress level experienced by nurses at the Regional Hospital of Pringsewu. This study is a quantitative study with a cross-sectional approach. The instrument used in this study was a questionnaire. Data collection was carried out on June 23-July 25, 2024 at the Regional Hospital of Pringsewu. The sample in this study amounted to 84 respondents who were taken using a random sampling technique. The data obtained were then analyzed using the gamma test.The results of the gamma test data analysis showed that there was a significant correlation between the work environment and work stress (p = 0.023 < 0.05) and there was a significant relationship between psychosocial hazards and work stress (p = 0.002 < 0.05). This study shows a significant correlation between the work environment and psychosocial hazards with work stress in the Regional Hospital of Pringsewu nurses. Nurses are encouraged to improve work management, while hospitals should strengthen supervision and provide adequate workplace facilities to support a healthy and productive work environment.